PERISTIWA TUTUR DALAM RITUAL TARI SEBLANG MASYARAKAT USING BANYUWANGI - Nafisatul Fuadah; Laurensius Salem; Martono Martono (Universitas Tanjungpura, 2022)
AbstractThis study aims to determine the form of speech and the socio-cultural function of aspeech event in the Seblang dance ritual ceremony of the Using community inBanyuwangi Regency. The research method used is descriptive with a qualitativeresearch form. The data source of this research is the participant community whofollows the events and activities directly from the object focused by the targetresearcher.The results showed that there were two types of speech forms in theSeblang dance ritual, namely, speech in preparation for the implementation of theSeblang dance ritual and speech in the implementation of the Seblang dance ritual. Asfor the speeches in preparation for the implementation of the ritual, there are fourtypes of speech events, namely speech during a meeting at the village head’s house,speech during a visit to the grave, speech during a visit to a spring, speech during themaking of Omprok Seblang. Furthermore, the speech during the implementation oftraditional rituals is that there is one type of speech that follows the ritual process tothe end.Then the social function of the traditional Seblang dance ritual is as a socialglue and as a medium of socialization. The traditional cultural functions of theSeblang dance, namely as a clean village salvation, inviting fertility, a means oftreating illnesses, and honoring ancestors. This research also discusses theimportance of traditional dance in the implementation of Indonesian languagelearning in SMA in the 2013 curriculum based on the observation report text.Keywords: Speech Event, Traditional Ceremony, Seblang Dance, Using Society,Learning Implementation.